2021
DOI: 10.3847/2041-8213/ac1681
|View full text |Cite
|
Sign up to set email alerts
|

Collisional Growth within the Solar System’s Primordial Planetesimal Disk and the Timing of the Giant Planet Instability

Abstract: The large-scale structure of the solar system has been shaped by a transient dynamical instability that may have been triggered by the interaction of the giants planets with a massive primordial disk of icy debris. In this work, we investigate the conditions under which this primordial disk could have coalesced into planets using analytic and numerical calculations. In particular, we perform numerical simulations of the solar system's early dynamical evolution that account for the viscous stirring and collisio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Moreover, the age of these interstellar comets could provide us with an estimate for the relative timing of the dynamical instabilities in exoplanetary systems. Based on theoretical modeling of the early timing of the instability in the solar system (Grav et al 2011;Buie et al 2015;Nesvorný et al 2018;Clement et al 2018Clement et al , 2019de Sousa et al 2020;Nesvorný et al 2021;Morgan et al 2021) and the recent discovery of an excess of free-floating planets in the Upper Scorpius <10 Myr stellar association (Miret-Roig et al 2022), it seems feasible that the majority of interstellar comets are ejected within the first <10 Myr of a planetary system's lifetime. If the majority of the population of interstellar comets formed interior to the CO snow line, this would imply that early giant planet migration is common in this region.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the age of these interstellar comets could provide us with an estimate for the relative timing of the dynamical instabilities in exoplanetary systems. Based on theoretical modeling of the early timing of the instability in the solar system (Grav et al 2011;Buie et al 2015;Nesvorný et al 2018;Clement et al 2018Clement et al , 2019de Sousa et al 2020;Nesvorný et al 2021;Morgan et al 2021) and the recent discovery of an excess of free-floating planets in the Upper Scorpius <10 Myr stellar association (Miret-Roig et al 2022), it seems feasible that the majority of interstellar comets are ejected within the first <10 Myr of a planetary system's lifetime. If the majority of the population of interstellar comets formed interior to the CO snow line, this would imply that early giant planet migration is common in this region.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, these works are associated with studying a last non-catastrophic stage in the Nice model. In this model, various schemes were discussed, including studies of both the planetary instability stage and the pre-instability stage (e.g., Tsiganis et al 2005;Morbidelli et al 2007;Batygin & Brown 2010;Levison et al 2011;Nesvorný & Morbidelli 2012;Reyes-Ruiz et al 2015;Quarles & Kaib 2019;Ribeiro de Sousa et al 2020;Morgan et al 2021). Fan & Batygin (2017) studied one case from Batygin et al (2011) that included a stage of the planetary instability and they compared simulations with a self-gravitating planetesimal disk and with a non-self-gravitating disk.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Fernández & Ip (1996) noted that objects of masses 1-5 M E are always produced along with Uranus and Neptune in their simulations. Recent numerical experiments of Morgan et al (2021) indicated that it is plausible for ∼1 M E objects to emerge within the primordial trans-Neptunian region on a ∼10 Myr timescale. tested the dependence of the "inclination instability" effect on the number N of massive objects in simulations.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous refinements were then brought to the instability model in order to properly reproduce the structure of the Solar System as we observe it today. The most recent advances favour a very early migration and instability (within 10 Myrs, or even immediately after dispersal of the gas disc), and no relation with the Late heavy bombardment (see Clement et al 2018Clement et al , 2021Nesvorný et al 2018;Morgan et al 2021).…”
Section: Introductionmentioning
confidence: 99%